Germinação de sementes de Rubus sellowii e micropropagação de Morus nigra - Duarte, Willian Naves (Universidade Federal de São Carlos, 2018)
Sexual and vegetative propagation are the main methods of perpetuating plant species. Despite its importance in propagation, seeds of some species do not germinate even under favorable conditions, as is the case of seeds of the genus Rubus, situation called dormancy. Experiments were carried out to characterize and overcome dormancy in R. sellowii seeds. During the seed imbibition process, was observed a barrier for water absorption. For the chemical scarification of the seeds, NaClO and H2SO4 were evaluated. NaClO was not efficient for tegument scarification. Treatment with H2SO4 for 20 min showed 50% seed germination and a higher rate of germination. It was also carried out the sowing, without scarification, in a tray containing substrate the base of pinus bark and kept in greenhouse. Seedling emergence started 70 days after sowing, reaching 50% after 370 days. Experiments were also carried out with the micropropagation of Morus nigra, considering the nonviability of commercial seed propagation. It was observed that in vitro cultivation of explants in the absence of phyto-regulators produced seedlings ready for the acclimatization phase. In the acclimatization, we tried to verify the best growing environment (growth room or greenhouse) and in vitro culture time. Growing for 28 days in the growing room resulted in plants with higher height (9.2 cm), number (4.8) and leaf diameter (3.23 cm), an essential condition for efficient acclimatization. For the somatic embryogenesis, calli of nodal explants of M. nigra were obtained with the use of naphthalene-acetic acid (ANA) or benzyladenine (BA), under light or dark conditions. Both presented similar callus induction rates. For the induction of somatic embryogenesis, twelve culture media were used for the induction of embryogenic calli. It was possible to obtain them in media containing BA, 2,4-D and coconut water. These were cultivated in liquid medium of maturation, in which they presented the development of globular structures of cream coloring. These globular structures have multiplied, acquiring green pigmentation when grown on sucrose or glucose as aviii carbon source. However, there was no subsequent development or regeneration in seedlings.
Rubus sellowii seed germination and Morus nigra micropropagation
Keywords: Dormência; Escarificação; Fitorreguladores; Cultivo in vitro; Embriogênese somática; Dormancy; Scarification; Plant growth regulator; In vitro culture; Somatic embryogenesis; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL